Comparative analysis of dentognathic pathologies in the Dmanisi mandibles. Issue 2 (26th February 2016) - Margvelashvili, Ann; Zollikofer, Christoph P.E.; Lordkipanidze, David; Tafforeau, Paul; Ponce de León, Marcia S.
ABSTRACT: Objectives: Due to the scarcity of the fossil record, in vivo changes in the dentognathic system of early Homo are typically documented at the level of individual fossil specimens, and it remains difficult to draw population‐level inferences about dietary habits, diet‐related activities and lifestyle from individual patterns of dentognathic alterations. The Plio‐Pleistocene hominin sample from Dmanisi (Georgia), dated to 1.77 million years ago, offers a unique opportunity to study in vivo changes in the dentognathic system of individuals belonging to a single paleodeme of early Homo . Materials and Methods: We analyze dentognathic pathologies in the Dmanisi sample, and in comparative samples of modern Australian and Greenlander hunter‐gatherer populations, applying clinical protocols of dentognathic diagnostics. Results: The Dmanisi hominins exhibit a similarly wide diversity and similar incidence of dentognathic pathologies as the modern human hunter‐gatherer population samples investigated here. Dmanisi differs from the modern population samples in several respects: At young age tooth wear is already advanced, and pathologies are more prevalent. At old age, hypercementosis is substantial. Conclusions: Results indicate that dentognathic pathologies and disease trajectories are largely similar in early Homo and modern humans, but that the disease load was higher in early Homo, probably as an effect of higher overall stress on the dentognathic system. Am J Phys Anthropol 160:229–253, 2016. © 2016 Wiley Periodicals, Inc.